2020
DOI: 10.1186/s13041-020-00650-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal zinc supplementation on the development of autism-associated behavioural and synaptic deficits in offspring Shank3-knockout mice

Abstract: Autism Spectrum Disorders (ASD) are characterised by deficits in social interactions and repetitive behaviours. Multiple ASD-associated mutations have been identified in the Shank family of proteins that play a critical role in the structure and plasticity of glutamatergic synapses, leading to impaired synapse function and the presentation of ASD-associated behavioural deficits in mice. Shank proteins are highly regulated by zinc, where zinc binds the Shank SAM domain to drive synaptic protein recruitment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 74 publications
(151 reference statements)
2
36
1
Order By: Relevance
“…Increased self grooming and other repetitive behaviors have been consistently reported in the models ex4-22|ALL [ 128 130 ], ex11|SH3 [ 123 ], ex13|PDZ [ 139 , 176 ], ex13-16|PDZ [ 83 , 90 , 155 , 159 , 160 , 162 164 , 166 , 168 , 181 183 ], ex14-16|PDZ [ 131 ], ex21|PRO [ 125 , 178 , 179 ], and ex11-21|SH3-PRO in rats [ 135 ]. Interestingly, in murine models ex21|PRO-InsG3680 [ 127 ] and ex8|ANK-Q321R [ 132 ], which mimick ASD-associated mutations, increased repetitive behavior was observed, whereas this was not the case in ex21|PRO-R1117X [ 127 ] mice, which harbor a schizophrenia-associated mutation.…”
Section: Main Textmentioning
confidence: 94%
See 2 more Smart Citations
“…Increased self grooming and other repetitive behaviors have been consistently reported in the models ex4-22|ALL [ 128 130 ], ex11|SH3 [ 123 ], ex13|PDZ [ 139 , 176 ], ex13-16|PDZ [ 83 , 90 , 155 , 159 , 160 , 162 164 , 166 , 168 , 181 183 ], ex14-16|PDZ [ 131 ], ex21|PRO [ 125 , 178 , 179 ], and ex11-21|SH3-PRO in rats [ 135 ]. Interestingly, in murine models ex21|PRO-InsG3680 [ 127 ] and ex8|ANK-Q321R [ 132 ], which mimick ASD-associated mutations, increased repetitive behavior was observed, whereas this was not the case in ex21|PRO-R1117X [ 127 ] mice, which harbor a schizophrenia-associated mutation.…”
Section: Main Textmentioning
confidence: 94%
“…In conditional KO-models targeting somatosensory neurons in ex13-16|PDZ-Advillin Cre or the caudal embryo, including the neural tube in ex13-16|PDZ-Cdx2 Cre abnormal social recognition was recapitulated [ 140 ]. Mixed evidence concerning the ability to recognize familiar conspecifics was observed in the model ex13-16|PDZ [ 90 , 155 , 161 , 164 , 166 , 168 ], where some studies found aberrant social recognition, while it seemed to be intact in others. No deficits of social recognition were found in the murine models ex4-9|ANK [ 78 , 80 , 167 ], ex9|ANK [ 82 , 175 ], ex14-16|PDZ [ 131 ], and ex21|PRO-InsG3728 [ 126 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers [72,73] studied the level of mercury in plasma, erythrocytes, reviews brain, hair, and urine of patients with ASD and healthy people and have established that impaired processes of detoxication and metal excretion in the sick people resulted in its accumulation in tissues, stimulation of neuroinflammation, and disease development. In other investigations, abnormal concentration of chromium, magnesium, and zinc in hair and/or blood have been detected in patients with ASD compared to the control group [74], special importance was attached to zinc deficiency [75][76][77].…”
Section: Genetic Hypothesesmentioning
confidence: 99%
“…Increasing dietary zinc in Shank3 mouse models of ASD reverses ASD-related behaviors in young mice and offspring of mice fed a zinc-supplemented diet (155,156). Whether these dietary zinc effects partially or fully stem from changes in the gut, including gut permeability or the gut microbiome, is of significant interest.…”
Section: Dietary Zinc and The Gastrointestinal Tract In Asdmentioning
confidence: 99%